1992
DOI: 10.1002/jts.2490050406
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia as a predictor of treatment response in post‐traumatic stress disorder

Abstract: FiFy-seven veterans with post-traumatic stress dhor&r (PTSD) completed the Alexithymia Provoked Response Questionnaire (APRQ) upon entering an 8-week randomized trial comparing pheneline, imipramine, and placebo. Low alexithymia on the APRQ significantly predicted improvement on the avoidance i t e m of the Impact of Events Scale (IES) particularly among patients treated with placebo, but was not associated with changes in the intrmwn items of the scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Secondary alexithymia in adults has received significant attention, as it has been examined in survivors of the Holocaust (Krystal, 1988), burn patients (Fukunishi, Chishima, & Anze, 1994), veterans (Kosten, Krystal, Giller, Frank, & Dan, 1992;Shipko, Alvarez, & Noviello, 1983), survivors of sexual victimization (Cloitre, Scarvalone, & Difede, 1997;Zeitlin, McNally, & Cassiday, 1993;Zlotnick, Mattia, & Zimmerman, 2001), and survivors of other forms of child maltreatment such as neglect and physical abuse (Modestin, Furrer, & Malti, 2005;Zlotnick et al, 2001). Furthermore, higher levels of alexithymia are related to the number of traumas and the greater severity of physical and emotional neglect (Zlotnick et al, 2001).…”
Section: Relationship Between Trauma and Alexithymiamentioning
confidence: 99%
“…Secondary alexithymia in adults has received significant attention, as it has been examined in survivors of the Holocaust (Krystal, 1988), burn patients (Fukunishi, Chishima, & Anze, 1994), veterans (Kosten, Krystal, Giller, Frank, & Dan, 1992;Shipko, Alvarez, & Noviello, 1983), survivors of sexual victimization (Cloitre, Scarvalone, & Difede, 1997;Zeitlin, McNally, & Cassiday, 1993;Zlotnick, Mattia, & Zimmerman, 2001), and survivors of other forms of child maltreatment such as neglect and physical abuse (Modestin, Furrer, & Malti, 2005;Zlotnick et al, 2001). Furthermore, higher levels of alexithymia are related to the number of traumas and the greater severity of physical and emotional neglect (Zlotnick et al, 2001).…”
Section: Relationship Between Trauma and Alexithymiamentioning
confidence: 99%
“…Should this be a survivor's frame of reference, the treatment of fear-based PTSD by therapeutic re-experiencing of trauma memories and associated emotions in a narrative-building and control-enhancing manner (e.g., therapeutic exposure) may need to be preceded and/or accompanied by intervention bolstering the survivor's capacities to ego-syntonically manage pathological dissociation and cognitive schemata, and primitive affect states and impulses. Furthermore, avoidant and emotional numbing symptomatology in DESNOS appears to be complicated by pathological dissociation (van der Kolk et al, 1996) and fragmentation of normal memory (van der Kolk & Fisler, 1995), as well as by the conscious avoidance and alexithymia characteristic of PTSD (Kosten, Krystal, Giller, Frank, & Dan, 1992). DESNOS also is typified by hypoarousal and a sense of impotent helplessness in the face of betrayal and malevolence, as opposed to the energizing (although dysfunctional) hyperarousal and hypervigilance characteristic of PTSD (van der Kolk et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The left hemisphere has been suggested to be involved in inhibiting emotional responses (Gainotti, Caltagirone, & Zoccolotti, 1993). In addition, other researchers (Alvarez & Shipko, 1991;Fukunishi, Chishima, & Anze, 1994;Hyer, Woods, Summers, Boudewyns, & Harrison, 1990;Kosten, Krystal, Giller, Frank, & Dan, 1992) have suggested that the right hemisphere inactivation involved in alexithymia considerably overlaps the emotional numbing and avoidance symptoms of PTSD. Henry, et al (1992) have found shared neuroendocrine patterns between PTSD and alexithymia and suggest that these patterns are the result of dissociation of cerebral hemispheres.…”
Section: Hypothesis 2: Bilateral Activation Hypothesismentioning
confidence: 98%